The antiparasite activity of bioactive isoflavans from Tabebuia chrysantha timber by-products (2022)
ABSTRACT: Parasitic diseases, including malaria, leishmaniasis, and Chagas disease, represent one of the most significant morbidity and mortality burdens worldwide, and many of them affect the most impoverished populations of the world but very few therapeutic options are available. Timber by-products are an interesting and emerging source of secondary metabolites. Tabebuia chrysantha (Jacq.) G. Nicholson 1887, is a tree of the Family Bignoniaceae, commonly known by the name of “guayacan Amarillo” (yellow guayacan). It is native to the dry forests of the American intertropical zone. Through bio-guided in vitro assays, high activities in the ethanolic extract (SQB-11) and metabolites from T. chrysantha sawdust were detected against Leishmania braziliensis, Trypanosoma cruzi and Plasmodium falciparum.